Construction and maintenance of elevated highway in Klang Valley / Norfariz Syahmi Othman - Othman, Norfariz Syahmi (Faculty of Architecture, Planning and Surveying, 2009)
The major towns are accessible by highway in the Kuala Lumpur. The highway networks are expanding at a slow rate. Hence, the maintenance of existing highway is of utmost importance. But it was found that some of the highways are badly deteriorated due to poor maintenance of the highway. A study was carried out with the objective to identify the main types of defects that frequently occur, the factors that cause the defect of elevated highway and also to identify the methods used for elevated highway repair. This study was carried out in Ampang Kuala Lumpur Elevated Highway (AKLEH). A total of 45 questionnaires were distributed and 42 of the questionnaires were received. The study was also carried out by interview. The data is analyzed using average index method and statistics. From the study the main types of defects that frequently occur are potholes, block cracks, raveling and rutting. The factors that cause the defects of roads are heavy traffic and excessive environmental condition. The method used for road repair is mainly by patching.